Translation, cultural adaptation and validation of the Systemic Lupus Erythematosus Activity Questionnaire (SLAQ) in a cohort of Italian systemic lupus erythematosus patients. (September 2018) - Tani, C; Vagelli, R; Stagnaro, C; Carli, L; Lorenzoni, V; Drago, F; Doherty, W; McSorley, M R; Marconcini, L; Della Rossa, A; Turchetti, G; Mosca, M
Introduction: The Systemic Lupus Erythematosus Activity Questionnaire (SLAQ) is a patient-reported instrument for the assessment of disease activity in systemic lupus erythematosus (SLE). The aims of the present study are translation, cultural adaptation and validation of an Italian version: the SLAQit. Methods: The process of translation and cultural adaptation followed published guidelines. SLAQit was pretested in a group of 35 SLE patients to evaluate acceptability, comprehension and feasibility. Internal consistency, test–retest validity and external validity were tested on consecutive SLE patients attending the clinic. Results: In total, 135 SLE patients were enrolled in this study. The pilot test provided a 99.9% response rate and demonstrated feasibility and comprehensibility of the questionnaire. A good internal consistency was found among the three components of the score (SLAQ score, numerical rating scale (NRS), patient global assessment question (PGA); α = 0.79). SLAQit showed very high reliability (test–retest α > 0.8). NRS and PGA showed a strong positive correlation with both Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) ( p = 0.002 and p < 0.001, respectively) and European Consensus Lupus Measurement (ECLAM) scores ( p = 0.01 and p < 0.001, respectively), while the SLAQ score did not. A significant agreement was observed between the physician's intention to treat and both the NRS and PGA scores, while no significant association was reported with the SLAQ score. Conclusions: SLAQit was demonstrated to be a reliable and valid instrument for self-assessment of disease activity in SLE patients.